The effect of Echinochloa crusgali density on the growth and development of paddy - Mohd Ikhwanuddin Khairuddin (2012)
An experiment was conducted at the Agro Park, Universiti Malaysia Kelantan, Jeli, Kelantan during the period from March to June 2012 to study the impact of different densities of barnyard grass (E. crusgali) on the growth and development of paddy. Five densities e.g. 0, 1, 2, 3 and 4 weds per pot was used in a pot (25 cm x 30 cm) containing a single rice plant. The effect of weed density on the plant height, number of tillers/plant, leaf area/plant and dry matter/plant were studied. From the experiment conducted, it shows that 14 weeds/m² (treatment 2) only is enough to cause massive reduction of yield by 44.19%. Farmers will have to deal with great loss of yield and money if no necessary action is taken to control the weed presence. The minimum point for farmers to take precaution is when the weed density approaching 15 weed/m² it can cause yield reduction to almost 50% which is cannot be tolerated. Plant height, number of tillers, leaf area and dry matter/plant were reduced linearly with the increase in weed density. The maximum number of weed per square meter with minimum percent of yield reduction is 5/m².